Cognitive decline in Parkinson's disease is associated with reduced complexity of EEG at baseline. Issue 2 (27th November 2020) - Keller, Sebastian M; Gschwandtner, Ute; Meyer, Antonia; Chaturvedi, Menorca; Roth, Volker; Fuhr, Peter
Abstract: Parkinson's disease is a neurodegenerative disorder requiring motor signs for diagnosis, but showing more widespread pathological alterations from its beginning. Compared to age-matched healthy individuals, patients with Parkinson's disease bear a 6-fold lifetime risk of dementia. For individualized counselling and treatment, prognostic biomarkers for assessing future cognitive deterioration in early stages of Parkinson's disease are needed. In a case–control study, 42 cognitively normal patients with Parkinson's disease were compared with 24 healthy control participants matched for age, sex and education. Tsallis entropy and band power of the δ, θ, α, β and γ-band were evaluated in baseline EEG at eyes-open and eyes-closed condition. As the θ-band showed the most pronounced differences between Parkinson's disease and healthy control groups, further analysis focussed on this band. Tsallis entropy was then compared across groups with 16 psychological test scores at baseline and follow-ups at 6 months and 3 years. In group comparison, patients with Parkinson's disease showed lower Tsallis entropy than healthy control participants. Cognitive deterioration at 3 years was correlated with Tsallis entropy in the eyes-open condition ( P  < 0.00079), whereas correlation at 6 months was not yet significant. Tsallis entropy measured in the eyes-closed condition did not correlate with cognitive outcome. In conclusion, the lower the EEG entropy levels at baseline in the eyes-open condition, the higher the probability of cognitive decline over 3 years. This makes Tsallis entropy a candidate prognostic biomarker for dementia in Parkinson's disease. The ability of the cortex to execute complex functions underlies cognitive health, whereas cognitive decline might clinically appear when compensatory capacity is exhausted. Graphical Abstract: Abstract : EEG-based Tsallis entropy measures signal complexity of brain rhythms. Low complexity of baseline EEG, measured in eyes-open condition, correlates with cognitive decline after 3 years in patients with Parkinson's disease. Tsallis entropy of EEG is, therefore, a candidate prognostic biomarker for cognition in Parkinson's disease.